Kebebasan Beragama Bagi kaum Muslimin Di Negeri Jerman - Zahrotunnimah Zahrotunnimah (ADALAH, 2019)
Abstract:Freedom of religion and worship is a basic right for every human being. So is the German Muslim community, which is the third largest religion in Germany after Catholicism and Protestantism. The German government has guaranteed the same freedom and equality for citizens and immigrants who are Muslim to carry out religious activities, even given the right to enter the Islamic curriculum in teaching in schools. Freedom which tends to be hard to find in the plains of Europe is now starting to open up. This paper wants to conduct elaborative research on the extent of religious freedom in Germany, especially for Muslims.Keywords: Freedom, Islam, Germany Abstrak:Kebebasan beragama dan menjalankan ibadah merupakan hak asasi bagi setiap manusia. Begitu pula dengan komunitas muslim Jerman yang merupakan agama terbesar ketiga di Jerman setelah Katolik dan Protestan, Pemerintah Jerman telah memberikan jaminan kebebasan dan kesetaraan yang sama bagi warga negara dan pendatang yang beragama Islam untuk melakukan kegiatan keagamaan, bahkan diberikan hak untuk memasukkan kurikulum agama Islam dalam pengajaran di sekolah-sekolah. Kebebasan yang cenderung susah didapatkan di dataran eropa saat ini sudah mulai terbuka. Tulisan ini ingin melakukan riset elaboratif sejauhmana kebebasan beragama di Jerman, khususnya bagi umat Islam.Kata Kunci: Kebebasan, Islam, Jerman